Wakaf Uang Untuk Infrastruktur Dalam Prespektif Hukum Islam - Fadhlullah Mudzakkir; Tarmidzi (Jurnal Hukum Islam, 2018)
This present study aims to explore cash waqf (Islamic endowment) for infrastructure in the perspective of Islamic law. Cash waqf may serve as an alternative to increase Indonesia’s economy and reduce the gap between rich and poor. It is worth mentioning to promote that one way to maximize the role of cash waqf is through infrastructure investment. A juridical and normative approach was designed in this library research. This study demonstrates that cash waqf is deemed sunnah (recommended) in relation to its maslahah (public benefits) and the Islamic law of cash waqf. Meanwhile, the Indonesian Ulema Council (MUI) issues a fatwa declaring that cash waqf is jawaz (permissible). This kind of waqf can only be distributed and used for the public interests that are allowed in sharia law, and the principal value of the cash waqf must be guaranteed for its sustainability. It implies that cash waqf may not be sold, granted, and/or inherited.